Fistula first, graft on arterialized vein second. (June 2015) - Galzerano, Giuseppe; Giubbolini, Michele; Setacci, Francesco; de Donato, Gianmarco; Sirignano, Pasqualino; Messina, Gabriele; Cappelli, Alessandro; Setacci, Carlo
Objectives: Arterovenous grafts (AVGs) present a feasible solution for creating a vascular access in patients who are unsuitable for autogenous fistula (AVF). The aim of this study is to assess the prevention rate of vein stenosis, placing a graft on an arterialized vein (GAV) instead of an anastomized AVG in a native vein (GNV). Methods: This was a cohort study conducted from January 2009 to November 2012. All consecutive patients who underwent AVG in our institution were included. All patients requiring a secondary intervention were also referred to our centre. Patients underwent ultrasound follow up at first and the every month. A Kaplan–Meier method was used; a Log-rank test was used to identify whether significant difference existed between GAV and GNV ( p < 0.05). Results: Forty-six grafts were placed. Twenty patients had arterialized receiving veins (group A), while 26 patients received an AVG immediately because they lacked autogenous veins suitable for fistula (group B).The average follow-up period was 16.1 months (range 0–41). The group A 41 months-patency rate was 84.3%, while group B was 43.7% ( p = 0.06). Secondary patency was similar in the two groups. Conclusions: Vein arterialization seems to prevent venous stenosis improving AVG-patency rate. More data are needed; however, the borderline p value encourages new studies.